ROENTGEN-ENDOVASCULAR EMBOLIZATION OF THE PORTAL VEIN BRANCHES AS A PATIENTS CONDITIONING FOR EXTENSIVE HEPATIC RESECTION - Kotenko, O G; Kondratyuk, V A; Fedorov, D A; Grinenko, A V; Korshak, A A; Gusev, A V; Popov, A O; Grigoryan, M S (Klinična hìrurgìâ (Kiïv), 2015)
The results of surgical treatment of 316 patients, suffering focal hepatic diseases, in whom for preoperative preparation a portal vein embolization (PVE) was performed, were analyzed. PVE was applied in a small planned hepatic residual volume. The patients have aged from 21 to 77 yrs, (57 ± 10.6) yrs at average. During (22 ± 7) days after the procedure a hypertrophy of a planned postresectional hepatic volume by 58.6% was observed, while a hypertrophy degree have depended on the embolization volume performed: 57.3%--after embolization of branches of C(V)-C(VIII) hepatic segments, 66%--the segments C(V)-C(VIII) + C(IV). In 281 (89%) patients the extensive hepatic resection was performed, a fatal postresection hepatic insufficiency was not observed. A three-year and five-year disease-free survival have constituted 43.8 and 16.4% accordingly. Thus, a PVE constitutes a miniinvasive intervention, permitting to achieve a planned residual hepatic volume, to expand a diapazon of application of radical extensive hepatic resection in patients, suffering focal hepatic diseases while a small planned residual hepatic volume.